2013 IEEE 8th International Conference on Industrial and Information Systems 2013
DOI: 10.1109/iciinfs.2013.6732000
|View full text |Cite
|
Sign up to set email alerts
|

Invariant properties of a locally salient dither pattern with a spatial-chromatic histogram

Abstract: Compacted Dither Pattern Code (CDPC) is a recently found feature which is successful in irregular shapes based visual depiction. Locally salient dither pattern feature is an attempt to expand the capability of CDPC for both regular and irregular shape based visual depiction. This paper presents an analysis of rotational and scale invariance property of locally salient dither pattern feature with a two dimensional spatialchromatic histogram, which expands the applicability of the visual feature. Experiments wer… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 14 publications
(14 reference statements)
0
9
0
Order By: Relevance
“…However, the algorithm was not competent enough to recognize an object with reasonable accuracy. Therefore, in this study, we introduce a completely novel technique to extract SDPF without sacrificing the gained benefits which have been described in [23][24][25].…”
Section: Salient Dither Pattern Feature Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the algorithm was not competent enough to recognize an object with reasonable accuracy. Therefore, in this study, we introduce a completely novel technique to extract SDPF without sacrificing the gained benefits which have been described in [23][24][25].…”
Section: Salient Dither Pattern Feature Extractionmentioning
confidence: 99%
“…The optimal amount of angle bins (k a ) were selected empirically, which will be discussed in the next section. The point allocation to angle bins is done as in (23).…”
Section: Orientation Normalizationmentioning
confidence: 99%
“…where h 1 and h 2 are the two histograms. In this study, the above kernel was implemented as mentioned in [10] using RBF kernel on Bhattachcharya distance between histograms, as shown in (6). k RBF h 1 ,h 2 =exp -d h 1 ,h s (6) where d h 1 ,h s is Bhattachcharya distance between h 1 and h 2 histograms.…”
Section: Proposed Clustering Approachmentioning
confidence: 99%
“…Such assumptions prevent the use of the algorithm for the majority of the videos due to uncertain behaviors of the salient objects. A previous study [4] has showed that a simple clustering technique can be used to cluster salient dither pattern (SDPF) features [6] by using temporal information and dither patterns, for semantic segmentation. However, it requires a human interaction for estimating the number of clusters (K) by inspecting a short sample of the video.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation